City Brand Personality – An International Concept with Regional Appliance in the Tourism Development Strategy - Oana Tugulea; Claudia Bobalca; Camelia Soponaru (CES Working Papers, 2013)
The personality of a city is an important concept to be created and evaluated by local administrators as this should be part of the touristic strategic approach. The aim of this paper is to create a research instrument that allows researchers to define the brand personality of a Romanian city. In order to use one instrument in a specific geographical area, the instrument has to be created using a qualitative research. Three focus groups were conducted in order to identify items to create the research instrument which is presented at the end of the paper. This research is a preliminary step for a future quantitative research that is intended to measure the city brand personality of the city of Iasi. The created instrument can be applied to any Romanian city.
Keywords: M39; 330; Brand personality; City Brand personality; focus group; personality traits; research instrument Romania